Begonia species (Begoniaceae) from Gunung Penrissen, Sarawak, Borneo, including two new species and a new subspecies - Yiing, Ling Chea; Sang, Julia; Kiew, Ruth (Phytotaxa, 2018)
Six species of Begonia are recorded from Gunung Penrissen in Padawan District, Sarawak, Malaysia including two new species (Begonia minutitepala and Begonia dasycaulis in Sect. Petermannia) and one new subspecies (Begonia natunaensis subsp. sarawakensis in Sect. Jackia). Detailed illustrated descriptions of the new taxa are provided together with a key to identify the species.